Becoming customer of choice in the healthcare supply chain - Purchase, S.; Butler, Bella; Alexander, Paul (School of Marketing, Edith Cowan University, 2011)
There is often a tacit assumption that in a buyer-seller relationship elements of value are the same for both parties. Using the concept of dynamic capabilities, and extending from existing research on customer perceptions of (supplier) value, this paper details a research project to investigate customer value from the supplier?s perspective. This has not been widely explored in the literature and in this paper an argument is developed to demonstrate that such a perception is a different, though equally important phenomenon to that for customers. The context of the study is the Australian healthcare supply chain in which there is a dearth of current information. Major research questions have been developed for the study, and the expected outcomes will include a ranked list of the elements of value that suppliers expect from buyers.